Analisis Pencapaian Program Imunisasi Dasar Lengkap Pada Masa Pandemi COVID-19 di Kabupaten Pesisir Selatan 2021 - Trianto, Ahmad Adi; Dasman, Hardisman; Lestari, Yuniar (Faculty of Medicine, Universitas Andalas, 2021)
Basic complete immunization coverage has decreased during the COVID-19 pandemic in Pesisir Selatan Regency. Objectives: To analyzed related factors of acceptance of basic complete immunization programs during the COVID-19 pandemic in Pesisir Selatan Regency. Methods: This research used qualitative methods with explanative design in three clusters of health center areas with 25 informants. The data were analyzed using the triangulation method through in-depth interviews and Focus Group Discussions (FGD). Results: The complete basic immunization has decreased in coverage during the COVID-19 pandemic because of the implementation of un maximum implementation due to lack of personnel accompanied by limited information media in remote areas causing lack of socialization, budget efficiency and no cooperation in each cluster, perceptions of halalness in rural areas, busyness parents in urban areas, non-compliance with health protocols in rural and remote areas, perceptions of no benefit in urban and remote areas, worry and fear of contamination COVID-19 in each cluster. Conclusion: The diversity of perceptions of each cluster causes a coverage has decreased of complete basic immunization during the COVID-19 pandemic in Pesisir Selatan Regency so that clustering on the implementation of complete basic immunization is needed.Keywords: complete basic immunization, coverage achievements, COVID-19